Financial Inclusion and Its Impact on Health: Empirical Evidence From Asia - Xiao, Wenling; Tao, Ran (Frontiers in Public Health, 2022)
Asian countries have shown remarkable progress in financial inclusion and have become the world's fastest-growing regions. However, the financial inclusion-human health nexus has not received much attention. This study contributes to the empirical literature by examining the effect of financial inclusion on population health using panel data from Asian countries from 2007 to 2019. Population health is measured by death rate and life expectancy at birth. Our study finding shows that digital financial inclusion increases life expectancy but decreases the death rate in Asia. At the same time, financial inclusion positively impacts life expectancy and has a negative impact on the death rate in Asia. Finding also suggests that Internet users, GDP, and FDI have improved population health by increasing life expectancy and decreasing the death rate. The results suggest some essential policy implications.